Hypoxia-inducible Factor-1alpha: Molecular-targeted Therapy for Hepatocellular Carcinoma - Dong, Z. Z.; Yao, M.; Wang, L.; Wu, W.; Gu, X.; Yao, D. F. (Mini Reviews in Medicinal Chemistry, 2013)
Hypoxia-inducible factor (HIF)-1α is over-expressed in hepatocellular carcinoma (HCC) and degraded by ubiquitin-proteasome pathways under normoxic conditions. Hepatocyte hypoxia enhances proliferation, angiogenesis, metastasis, chemoresistance, and radioresistance of HCC. The importance role of HIF-1α expression in HCC may improve the prognostic and therapeutic technique. This article reviews the HIF-1α expression and its gene during the rat HCC development, the level of HIF-1α expression in HCC patients, and the effect of silencing HIF-1α gene by miRNA on inhibition of HepG2 cell proliferation.
Keywords: angiopoietin-2